Beautiful boy [videorecording (DVD)] - Ku, Shawn; Ku, Shawn; Sheen, Michael; Bello, Maria, 1967-; Nichols, Austin, 1980-; Tudyk, Alan; Bloodgood, Moon; Gallner, Kyle; Meat Loaf (Vocalist), 1947- (Anchor Bay Entertainment, 2011)
Bill and Kate hopelessly try to find some hint of an explanation after finding out that their only son committed a mass shooting at his university before taking his own life. They struggle numbly through the funeral, the media onslaught, and the awkward pity from relatives and friends. Their already strained marriage is tested as they realize all they have left with each other is their shared grief and confusion, and the unfortunate legacy of their son.